1987
DOI: 10.2105/ajph.77.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Associations between smoking and body weight in the US population: analysis of NHANES II.

Abstract: Recent recommendations for increases in desirable body weights are based upon studies which did not consider the potential confounding effect of cigarette consumption on body weight. We investigated the relation between tobacco use and several anthropometric measurements in 12,103 men and women 19-74 years of age in the United States examined between 1976 and 1980 during the Second National Health and Nutrition Examination Survey (NHANES II). Cigarette smokers weighed less (mean ± standard error = 69.8 ± 0.2 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
242
4
9

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(276 citation statements)
references
References 28 publications
21
242
4
9
Order By: Relevance
“…First, other factors, such as sports activity or physical activity, might confound the relationship between smoking and OA. Second, recent research has shown that smokers are more likely to maintain low weights over time, as opposed to nonsmokers, who tend to gain weight over time (11); therefore, weight change might confound the smoking-OA association. Finally, we were concerned that weight, a potent risk factor for OA (12), might have a nonlinear relationship with disease and that nonlinear modeling of weight might be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…First, other factors, such as sports activity or physical activity, might confound the relationship between smoking and OA. Second, recent research has shown that smokers are more likely to maintain low weights over time, as opposed to nonsmokers, who tend to gain weight over time (11); therefore, weight change might confound the smoking-OA association. Finally, we were concerned that weight, a potent risk factor for OA (12), might have a nonlinear relationship with disease and that nonlinear modeling of weight might be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the present study are in line with many other studies. In fact, many studies found that current smokers are more likely to have higher WC [26][27][28] values than nonsmokers. However, Berlin et al found that high WC values were less frequent among current smokers [29].…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Then again, smoking tends to be similarly unable to explain geographical variation in other diseases, such as ischaemic heart disease, 33 ± 35 cerebrovascular disease, 36 or chronic obstructive pulmonary disease, 37 for which it is a known risk factor. As regards alcohol consumption, the situation is somewhat different, since the association between alcohol and body weight has not been unequivocally established in the scienti®c literature on the subject.…”
Section: Discussionmentioning
confidence: 99%